2003
DOI: 10.1159/000068288
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Contact Allergenic Haptens to Amino Acid Residues in a Model Carrier Peptide, and Characterization of Formed Peptide-Hapten Adducts<sup>1</sup>

Abstract: The type of chemical reaction between hapten and carrier protein in the formation of a complete antigen in vivo giving rise to an allergic contact dermatitis (ACD, type IV allergy) is essentially unknown. About 4,000 low-molecular organic compounds are known to have allergenic properties. α,β-Unsaturated carbonyl structures are frequently present among these compounds. Haptens giving rise to antibody formation and type I allergy have been shown to add predominantly to lysine in the carrier protein. In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 24 publications
1
54
2
Order By: Relevance
“…This is because the reactivity of acrylates and methacrylates with sulfhydryl groups such as GSH and cysteine-containing polypeptides is closely related to their toxicity 5,6) . Besides, methacrylates with α, β-unsaturated carbonyl structures have been reported to possess allergenic properties due to their depletion of GSH 8) . In dentistry, the toxicity of triethylene glycol dimethacrylate (TEGDMA) has been shown to be related to its Received Jun 9, 2009: Accepted Jul 24, 2009 GSH 4,9) reactivity with , resulting in almost total depletion of intracellular GSH via Michael addition predominantly 9) .…”
Section: Introductionmentioning
confidence: 99%
“…This is because the reactivity of acrylates and methacrylates with sulfhydryl groups such as GSH and cysteine-containing polypeptides is closely related to their toxicity 5,6) . Besides, methacrylates with α, β-unsaturated carbonyl structures have been reported to possess allergenic properties due to their depletion of GSH 8) . In dentistry, the toxicity of triethylene glycol dimethacrylate (TEGDMA) has been shown to be related to its Received Jun 9, 2009: Accepted Jul 24, 2009 GSH 4,9) reactivity with , resulting in almost total depletion of intracellular GSH via Michael addition predominantly 9) .…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest a mechanism of action in which piceatannol enters into cells and is subsequently oxidized into an electrophilic O-benzoquinone that readily reacts with nucleophilic atoms from the amino acid side chains of Cbl (38). This would then lead to the cross-linking of Cbl, explaining the smearing observed by Western blotting after piceatannol treatment (refs.…”
Section: Discussionmentioning
confidence: 88%
“…We hypothesized that in vitro most proteins would be sensitive to piceatannol-induced protein loss, considering that we have been unable to identify a specific region of Cbl that led to its sensitivity to piceatannol (Fig. 1A) and that there are many different amino acids with nucleophilic atoms in their side chains, none of which are unique to Cbl, which could react with O-benzoquinones including cysteine, methionine, histidine, tryptophan, serine, tyrosine, lysine, arginine, and proline (38). Western blotting of in vitro reactions containing c-Cbl, c-Src, Lyn, or PDGFRh confirmed that, similar to c-Cbl, all of these proteins were lost in the presence of piceatannol and ROS (Fig.…”
Section: Piceatannol Induces the Selective Loss Of Proteins Otherthanmentioning
confidence: 99%
“…94% agreement with in vivo data on 18 chemicals ECVAM pre-validation on-going Reactivity Assay) (Ahlfors et al, 2003).…”
Section: Dpra (Direct Peptidementioning
confidence: 79%